Counseling on Diet Programs to Minimize the Risk of Hypertension in Poris Plawad Village, Cipondoh Sub-District: Penyuluhan Program Diet Untuk Meminimalisir Risiko Hipertensi di Kelurahan Poris Plawad, Kecamatan Cipondoh - Rahmania, Sarah; Wijoyo, Eriyono Budi (Ruang Ide Publisher, 2024)
Hypertension is a serious medical condition that may increase the risk of heart disease and stroke, and is one of the global health priorities. In Indonesia, many people suffer from hypertension, and they are unaware of the problem because it may have no warning symptoms. So to minimize the impact, a hypertension diet needs to be done. Counseling really needs to be conducted to help increase public knowledge regarding the implementation of the hypertension diet. The results of the counseling showed that people were aware of the importance of a hypertension diet, because this disease may trigger other diseases. Undergoing a low-sodium diet and avoiding foods that trigger hypertension need to be accompanied by regular exercise. The results of the counseling showed that 70% of the counseling participants had knowledge of the hypertension diet, so that the counseling could be said to have been maximized. However, similar counseling needs to be further carried out on a wider scope to generate greater benefits.